Dinamika Perkembangan Pasar Nagari di Luhak Agam: Studi Tentang Pasar Baso 1980-2021 - Yulia Rahmadhani; Etmi Hardi (Jurusan Sejarah FIS UNP, 2023)
This study discusses the Nagari Market as well as the Syarikat Baso Market. Baso Market is located in Kenagarian Tabek Panjang, Baso Di strict, Luhak Agam, West Sumatra. This research discusses the years 1980-2021. The focus of the study of this research discusses the history and development of the Baso Market and discusses the development of Baso Market traders in 1980-2021. The purpose of this study is to reveal the history of Baso Market, the development of Baso Market in Luhak Agam starting from the physical building and economic activity in Baso Market. This research includes historical qualitative research, using historical methods, which includes four stages, namely: Heuristics, namely searching for historical data, source criticism (the stage of selecting historical data), interpretation (interpretation of historical data) and histiography (the stages of writing history). . From the discussion it can be seen that First, Pasar Baso is known as the banana market because in 1980 many banana traders were selling bananas, then the history of Baso Market, namely As with other kelararan markets in Agam Koto Tuo, Baso Market was founded on a call from the Minangkabau Sultanate I, namely Alif Khalifatullah in 1403 AD. Second, the development of Baso Market in terms of physical buildings, the buildings at Baso Market underwent first changes from 1980-2021 due to the increasing number of traders and buyers. Third, the development of traders from the type of merchandise that changes due to reasons of demand for the needs of the people in the Baso District area which change every yearKeyword: History, development, traders, Market Baso.